Anticancer and antifungal efficiencies of purified chitinase produced from Trichoderma viride under submerged fermentation - Isaac, George Saad; Abu-Tahon, Medhat Ahmed (Journal of general and applied microbiology, 2020)
Trichoderma viride AUMC 13021 isolated from Mangrove soil of Ras Mohammed protected area at Sharm El-Sheikh, Egypt, was optimized to promote chitinase activity under submerged fermentation. The maximum enzyme yield (38.33 U/mg protein) was obtained at 1.4% of colloidal chitin, 96 h of incubation, 35°C, pH 6.5 and 125, rpm and using maltose (1%) and yeast extract (1%) as supplementation of salt basal medium. The enzyme has been purified with an overall yield of 73.1% and 5.48 purification fold, and a specific activity of 210.16 U/mg protein. The molecular mass of the purified chitinase was 62 kDa. Maximal activity of chitinase was recorded at pH 6.5 and 40°C. The highest activity was recorded in the case of colloidal chitin, with an apparent Km value of 6.66 mg/ml and Vmax of 90.8 U/ml. The purified chitinase was activated by Ca2+ and Mn2+ while the activity was inhibited by Hg2+, Zn2+, Cu2+, Co2+, dodecyl sulphate and EDTA. In vivo, the median lethal dose (LD50) was approximately 18.43 mg/kg body weight of Sprague Dawley rats. MTT assay showed that the purified chitinase has a toxic effect to MCF7 with an IC50 value 20 μg/ml, and HCT-116 cell lines with an IC50 value 44 μg/ml. Moreover, the purified enzyme showed significant antifungal activity against Fusarium oxysporum f. sp. lycopersici race 3 the causal agent of tomato wilt.